2016
DOI: 10.1111/jnc.13834
|View full text |Cite
|
Sign up to set email alerts
|

C‐terminal of human histamine H1receptors regulates their agonist‐induced clathrin‐mediated internalization and G‐protein signaling

Abstract: It has been suggested that the agonist-induced internalization of G-protein-coupled receptors from the cell surface into intracellular compartments regulates cellular responsiveness. We previously reported that G -protein-coupled human histamine H receptors internalized via clathrin-dependent mechanisms upon stimulation with histamine. However, the molecular determinants of H receptors responsible for agonist-induced internalization remain unclear. In this study, we evaluated the roles of the intracellular C-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
1
14
0
2
Order By: Relevance
“…Many studies have suggested that agonist-induced internalization of G-protein coupled receptors (GPCRs) from the cell surface into intracellular compartments regulates cellular responsiveness [58,59]. The multiple incremental suboptimal antigen doses administrated during DS may lead to the release of small amounts of histamine that would bind to receptors and subsequently induce internalization of the receptors.…”
Section: Mast Cells: Positive and Negative Regulation Is Relevant mentioning
confidence: 99%
“…Many studies have suggested that agonist-induced internalization of G-protein coupled receptors (GPCRs) from the cell surface into intracellular compartments regulates cellular responsiveness [58,59]. The multiple incremental suboptimal antigen doses administrated during DS may lead to the release of small amounts of histamine that would bind to receptors and subsequently induce internalization of the receptors.…”
Section: Mast Cells: Positive and Negative Regulation Is Relevant mentioning
confidence: 99%
“…In order to clarify whether H 1 receptor molecules are lost after the ionomycin treatment, we used CHO cells expressing human histamine H 1 receptors tagged with HA at the N terminus (Hishinuma et al . ), in which H 1 receptors were detected by an anti‐HA antibody instead of [ 3 H]mepyramine (Fig. ).…”
Section: Resultsmentioning
confidence: 97%
“…The binding of [ 3 H]mepyramine, a cell‐penetrant radioligand for H 1 receptors, to all cellular and cell‐surface H 1 receptors was detected, using mepyramine and pirdonium (a hydrophilic H 1 receptor ligand with a permanently charged quaternary ammonium group), respectively (Hishinuma et al . ). Briefly, aliquots (0.1 mL) of control and ionomycin‐treated cells (circa 3 × 10 5 cells, approximately 0.2–0.3 mg whole cell protein) were suspended in ice‐cold normal HEPES buffer (final volume 1 mL) and then incubated with 0.1–10 nM [ 3 H]mepyramine in the presence or absence of 10 μM mepyramine or 2 μM pirdonium at 4°C for 24 h in initial saturation experiments.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations